Ciało jako przedmiot i podmiot procesu wychowania seksualnego - Babik Marek (Jesuit University Ignatianum in Krakow, 2017)
Former deﬁ nitions of education and pedagogy refer merely to the problem of a child living on various stages of development. They do not touch pedagogical functioning of parents (teachers, society) before child's birth. Similar is the case with studies concerning subjectivity and objectivity of human behaviours. They talk about an existing person. It seems that demanding appropriate motives for giving someone life entitles you to call for broadening this view to include motivating issues in the ﬁ eld of procreation, thereby broadening a look on human subjectivity. This additional range would be considering the subjectivity of a child whose conception is being planned. On pedagogical grounds, such actions could be described as pre-pedagogy (pre-education). Within the scope of this notion, one could mention all the actions taken by parents (educators, society) demanding respect for the subjectivity of a child not yet conceived. Accepting such a postulate results as a consequence in the necessity to verify general educational actions with special consideration for sexual education. Sexual intercourse from this perspective ceases to be merely an act of a man and a woman, but becomes an event requiring taking into account the subjectivity of an even potential child.